Implementation of Online Gampong in The City Of Lhokseumawe - Fazil, Muhammad; Fahmi, Asrul (International Journal of Engineering, Science and Information Technology, 2021)
This study is entitled "Implementation of Gampong Online in Lhokseumawe City". Where the strengthening of information and communication technology is still considered a luxurious facility and requires very large costs, so only a small part of the village government has obtained it. The wide gap between the size of the budget needs and the limited budget that can be provided gives rise to budget allocations that lead to physical activities for the development of rural infrastructure alone without looking at the increasingly rapid technological developments and increasing the capacity of village apparatus resources to support the current government system. both in the administrative system, public services as well as on matters relating to community business development. This study aims to see and describe the implementation of technology to present online gampongs with basic information and communication technology training activities for gampong governments in Lhokseumawe City. A descriptive qualitative approach with observation and documentation data collection techniques has been carried out in this study with field assessments in 3 (three) Gampongs in the Lhokseumawe city area to see the application of technology, determine strategy, socialize and provide information and communication technology introduction materials. The results of the study found that training for 3 (three) gampongs in the Lhokseumawe city government, namely Gampong Hagu Barat Laot, Gampong Hagu Teungoh and Gampong Hagu Selatan, had provided an understanding and awareness of the importance of using information and communication technology in gampong government for the smooth running of public services, public relations and public relations. internal organization as well as improving the business of the village community in the field of technology, where technology can help the village government connect with the city government and the village community online.